Monitoring and evaluation of the meat diseases of the Aberdeen-Angus breed in Ukraine - Колісник, О. І.; Прудніков, В. Г.; Криворучко, Ю. І. (Scientific Progress & Innovations, 2018)
As a result of the research, the issue of the number of breeding cattle of imported Aberdeen-Angus meat breed in Ukraine was studied. The number of breeding plants and breeding products, which specialize in its breeding, has been determined to date. The total number of Aberdeen- Angus in Ukraine in 2017 was 6.520 heads, including cows. At the same time, the number of livestock in both the breeding plants and the breeding farms decreased during the period under review. So, if the Aberdin population had 7649 animals in 2014, then in 2017 it was 6520. Accordingly, the number of enterprises where the cattle of this breed was bred decreased. The largest number of livestock is concentrated in OOO «Buffalo» in Volyn’ region – 1350 heads, including 625 cows. It should also be noted the negative trend of a decrease in both livestock and households. For example, in Zhytomyr region, where in 2015 there were 251 heads of aberdines, at present it is not cultivated by it. For four years out of 20 farms that specialized in this breed, there are 17 in 11 regions of Ukraine. It should be noted that there are areas that do not cultivate Aberdeen-Angus at all, although there are conditions for this. The main indicator of the meat productivity of beef cattle is the living weight. As a result of the analysis it was established that the maximum live weight of full-fat cows is 620 kg, and the minimum weight is 475 kg. In most farms specialize in the breeding of large-type Aberdeen-Angus, and in the rest – small type of British origin. The yield of calves per 100 cows ranges from 65 to 100 %. Live weight of calves at birth on average in Ukraine: heifers – 26.5 kg, bull-calves – 29.4 kg. It again confirms the fecundity of the Aberdeen-Angus. The average daily gain on the suckling is on the average 841 g, after weaning – 887 g. In the economy of beef cattle breeding, the milk of cows is important, on which the calves live after weaning at 7–8 months of age. Milk of cows is low and is in the range of 165–208 kg, which affects the calves' live weight at weaning and it is also a disadvantage of the breed. Given its heterogeneity in origin (British and American), productive indicators and existing shortcomings, a program was developed to create a consolidated competitive Ukrainian Angus meat breed. The program provides for the breeding of a new breed as a result of purebred breeding using rigid selection and selection. Today, work is actively being carried out to create it in Agro-Novoselivka 2009 agrofirm in Kharkiv region. The native breed is created in conditions of resource-saving technology, which in the technological process does not provide for the use of premises, that is, close to the natural conditions.